The HIV Entry Inhibitors Revisited - Leonard, J. T.; Roy, Kunal (Current Medicinal Chemistry, 2006)
The new generation of antiviral drugs intended to counter HIV-1 entry into susceptible cells is emerging swiftly. The antiviral agents that inhibit HIV entry to the target cells (denoted as HIV entry inhibitors) are already in different phases of clinical trials. Operating early in the viral life cycle, they prevent viral entry, and have a novel, highly specific mechanism of action with a low toxicity profile. Entry inhibitors have different toxicity and resistance profiles than the existing reverse transcriptase and protease inhibitors. Some of these compounds demonstrated in vitro synergism with other classes of antivirals, thus offering the rationale for their combination in therapies for HIV-infected individuals. It is worth focusing on recent developments in HIV entry inhibitors, as most of the current drug regimens suffer from the events of developing resistance against existing combination therapies. Recent advances in the understanding of the cellular and molecular mechanisms of HIV-1 entry provide the basis for novel therapeutic strategies that prevent viral penetration of the target cell-membrane, while reducing detrimental virus and treatment effects on cells and prolonging virion exposure to immune defenses. A number of potential sites for therapeutic intervention become accessible during the narrow window between virus attachment and the subsequent fusion of viral envelope with the cell membrane. The HIV-1 coreceptors are particularly attractive from the perspective of identifying new antiviral compounds, since they are seven-transmembrane motif G protein-coupled receptors (GPCRs), a family of proteins that is a well-validated target for drug development. Among the many chemokine receptors that can mediate HIV-1 entry in vitro, only CCR5 and CXCR4 are of frontline pharmacological importance. In particular, CCR5 is essential for viral transmission and replication during the early and clinically latent phase of disease. Several small-molecule antagonists of CCR5 and CXCR4 that block chemokine binding and HIV-1 entry have been identified in recent years. Considerable advances have been made in the last years in the design of derivatives acting as inhibitors of HIV entry. The molecular mechanism involved in viral entry, the structural and functional aspects of entry inhibitors are reviewed here. We have also summarized the recent insights into how small-molecule antagonists interact with CCR5 and CXCR4, focusing on drug development programs that are well documented in the scientific literature. An overview of the entry inhibitors that are in preclinical or early clinical development, and the Quantitative Structure-Activity Relationships (QSAR) studies reported for the coreceptor antagonists are also be presented.
Keywords: CCR5 Antagonists